PERANCANGAN ULANG JEMBATAN BENGAWAN SOLO LAMA CEPU – BLORA - Paizal Pebriyanto; Adina Permatasari; Bambang Riyanto; Bambang Pudjianto (Jurnal Karya Teknik Sipil, 2016)
Central Java and East Java is separated by the Bengawan Solo River. To support the activities of transportation which across Central Java and East Java, was Bengawan Solo Bridge built on the road Cepu -Padangan on Blora KM SMG 160.09. Bengawan Solo Bridge consists of two bridges, Bengawan Solo Baru Bridge and Bengawan Solo Lama Bridge. Since 1994, only Bengawan Solo Baru Bridge which operated, while Bengawan Solo Lama Bridge had no function anymore because the condition is not feasible. Along with the growth and movement patterns of traffic, it was found that in certain conditions, especially during peak hours, often seen queues of vehicles will cross the Bengawan Solo Baru Bridge. This is based on the value of Degree of Saturation (DS) Bengawan Solo Baru Bridge is 0.78 (> 0.75), which indicates the traffic condition is already unstable. Therefore, operating Bengawan Solo Lama Bridge again can be a solution to the congestion and potential overload that occurs. However, to realize that, Bengawan Solo Lama Bridge needs to be redesigned considering exsisting condition is not feasible and the age of the bridge is already very old. As the technical and aesthetic considerations, Bengawan Solo Lama Bridge is designed by considering the condition of Bengawan Solo Baru bridge so that the Bengawan Solo Lama Bridge is planned use steel structures for the upper structure and reinforced concrete structures for bottom structure. After that, Bengawan Solo Lama Bridge is designed to serve traffic from Cepu to Padangan with the type of road 2/1 UD (two-lane one-way) which has a width of 6 meters and width of sidewalks 2 x 1 meter. The planning of traffic aspects use a life design for 25 years with the traffic growth by 2,472% per year. Implementation of Construction is at a cost of 33.4 billion. The scope of the planned bridge elements in this thesis includes work for the overall structure bridge and approach bridge.